Scorpion Venom Heat–Resistant Synthesized Peptide Increases Stress Resistance and Extends the Lifespan of Caenorhabditis elegans via the Insulin/IGF-1-Like Signal Pathway - Wang, Ying-Zi; Guo, Song-Yu; Kong, Rui-Li; Sui, Ao-Ran; Wang, Zhen-Hua; Guan, Rong-Xiao; Supratik, Kundu; Zhao, Jie; Li, Shao (Frontiers in Pharmacology, 2022)
Improving healthy life expectancy by targeting aging-related pathological changes has been the spotlight of geroscience. Scorpions have been used in traditional medicine in Asia and Africa for a long time. We have isolated heat-resistant peptides from scorpion venom of Buthusmartensii Karsch (SVHRP) and found that SVHRP can attenuate microglia activation and protect Caenorhabditis elegans against β-Amyloid toxicity. Based on the amino acid sequence of these peptides, scorpion venom heat-resistant synthesized peptide (SVHRSP) was prepared by polypeptide synthesis technology. In the present study, we used Caenorhabditis elegans (C. elegans) as a model organism to assess the longevity-related effects and underlying molecular mechanisms of SVHRSP in vivo. The results showed that SVHRSP could prolong the lifespan of worms and significantly improve the age-related physiological functions of worms. SVHRSP increases the survival rate of larvae under oxidative and heat stress, and decreases the level of reactive oxygen species (ROS) and fat accumulation in vivo. Using gene-specific mutation of C. elegans, we found that SVHRSP-mediated prolongation of life depends on Daf-2, Daf-16, Skn-1 and Hsf-1 genes. These results indicate that the anti-aging mechanism of SVHRSP in nematodes might be mediated by the insulin/insulin-like growth factor-1 (IIS) signaling pathway. Meanwhile, SVHRSP could also up-regulate the expression of stress-inducing genes Hsp-16.2, Sod-3, Gei-7 and Ctl-1 associated with aging. In general, our study may have important implications for the use of SVHRSP to promote healthy aging and provide strategies for research and development of drugs to treat age-related diseases.